1995
DOI: 10.1029/94gl02403
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal event plumes from the coaxial seafloor eruption site, Juan de Fuca Ridge

Abstract: The episodic magmatic intrusions that accompany seafloor spreading can profoundly affect the discharge of hydrothermal heat and fluid. A rapid field response to the acoustic detection of seismic activity on the CoAxial segment of the Juan de Fuca Ridge, June/July 1993, provided the opportunity to conduct a unique series of observations of hydrothermal event plumes. Between July 3 and 26 we detected at least three event plumes ranging in plume volume from 1.3 to 4 × 1010 m³, and in excess heat from 2.2 to 12.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(47 citation statements)
references
References 12 publications
2
45
0
Order By: Relevance
“…A flow with a volume of 5 x 10 6 m 3 was associated with a 40 km long dike that propagated over a two-day period (Baker et al, 1995). Cherkaoui et al (1997) used data from studies of the water column above the dike and concluded that the dike lost most of its heat within three months of intrusion into permeable rock that was saturated with seawater.…”
Section: Co 2 and H 2 Production In Diking-eruptive Eventsmentioning
confidence: 99%
“…A flow with a volume of 5 x 10 6 m 3 was associated with a 40 km long dike that propagated over a two-day period (Baker et al, 1995). Cherkaoui et al (1997) used data from studies of the water column above the dike and concluded that the dike lost most of its heat within three months of intrusion into permeable rock that was saturated with seawater.…”
Section: Co 2 and H 2 Production In Diking-eruptive Eventsmentioning
confidence: 99%
“…They concluded that the megaplumes formed over 2±20 d from a ®ssure 2,000±200 m long. Subsequently, additional detached megaplumes have been identi®ed in the North Fiji basin 9 , the Eastern Manus basin 10 and further north on the Juan de Fuca ridge 11 .…”
Section: Previous Observations and Modelsmentioning
confidence: 99%
“…0148-0227/97/97JB-02123509.00 The CoAxial event of June 1993 is the first diking event to be detected remotely and monitored by the SOSUS hydrophone arrays ; it is also the first submarine diking event for which seafloor observations are correlated with measurements in the hydrothermal plumes [Baker et al, 1995a] and with seismic data which constrain the temporal and spatial characteristics of dike emplacement [Fox et Along with the seafloor observations, extensive water column measurements were obtained during the initial field response Baker et al, 1995a]. Temperature and light attenuation anomalies were mapped along the segment axis using a conductivity-temperature-depth (CTD) and transmissometer package which was cycled vertically while being towed through the water.…”
Section: Paper Number 97jb02123mentioning
confidence: 99%